Is implant sonication useful when screening for infection in conversion of prior hip fracture fixation to total hip arthroplasty?. Issue 9 (September 2021) - Palmowski, Yannick; Pumberger, Matthias; Perka, Carsten; Hardt, Sebastian; Hipfl, Christian
Objective: To examine sonication results in presumed aseptic conversion total hip arthroplasty (THA) after hip fracture fixation and to evaluate its implications on the treatment outcome. Methods: This retrospective cohort study reviewed the data from presumed aseptic patients that underwent conversion of prior internal fixation of proximal femoral fractures to THA between 2012 and 2018. Microbiological analysis was performed using sonication of osteosynthesis material and tissue samples. Treatment outcome including the occurrence of periprosthetic joint infection (PJI) was recorded. Results: A total of 32 patients were included in the study. Of these, five patients (15.6%) had positive intraoperative cultures. The mean follow-up following conversion THA was 43.0 months (range, 19.0–91.5 months). Sonication was positive in three patients (9.4%), all of whom were deemed contaminated and did not develop PJI. Tissue cultures were positive in two patients (6.3%). One patient with Enterococcus faecalis received antibiotic treatment and did not develop PJI. Another patient with growth of Cutibacterium acnes that was initially classified as a contaminant later developed acute PJI caused by the same pathogen. Overall, PJI occurred in two patients (6.3%) after conversion THA. Conclusion: Sonication of internal fixation devices did not add diagnostic value in clinically aseptic conversion THA. Further studies are needed to better understand the relevance of unexpected positive cultures, and to develop diagnostic criteria for the management of these patients.